2006
DOI: 10.1677/jme.1.01932
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the thyrostimulin subunits, glycoprotein  2 and  5 in the rat pituitary

Abstract: Two glycoprotein hormone subunits, (glycoprotein hormone a2-subunit GPA2) and (glycoprotein hormone b5-subunit GPB5) have been recently discovered which, when expressed in vitro, heterodimerize to form a new hormone called thyrostimulin. Thyrostimulin activates the thyroid-stimulating hormone receptor (TSHR) and has thyrotropic activity. Immunological studies have indicated that both subunits co-localize in pituitary cells. To explore the function of thyrostimulin in the rat, we have cloned rat GPA2 and GPB5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…Such a role may be observed in the human pituitary gland, where GPA2 and GPB5 co-localize (Nagasaki et al 2006). Interestingly, TSHR is also present on folliculo-stellate cells of the human anterior pituitary (Brokken et al 2005).…”
Section: Th E Unique Structure Of Thyrostimulinmentioning
confidence: 83%
See 2 more Smart Citations
“…Such a role may be observed in the human pituitary gland, where GPA2 and GPB5 co-localize (Nagasaki et al 2006). Interestingly, TSHR is also present on folliculo-stellate cells of the human anterior pituitary (Brokken et al 2005).…”
Section: Th E Unique Structure Of Thyrostimulinmentioning
confidence: 83%
“…Interestingly, GPA2 does not heterodimerize with any of the other four known β subunits, whilst GPB5 does not heterodimerize with GPA1 (Nagasaki et al 2006). Even though, the GPA1 and GPA2 have only 35% primary sequence identity.…”
Section: Th E Unique Structure Of Thyrostimulinmentioning
confidence: 99%
See 1 more Smart Citation
“…thyrostimulin; type II deiodinase; inflammation; thyroid hormone THE PUTATIVE GLYCOPROTEIN HORMONE thyrostimulin, comprising ␣2-(GPA2) and ␤5-(GPB5) subunits, has been reported to activate the thyroid-stimulating hormone (TSH) receptor (TSHR). Thyrostimulin does not play a major role in the classical feedback regulation of the hypothalamo-pituitarythyroid (HPT) axis, as GPB5 knockout (GPB5 Ϫ/Ϫ ) mice do not have an abnormal thyroid phenotype and transcription of GPB5 is not regulated by thyroid hormone or thyrotropin-releasing hormone (TRH) (14,20). Furthermore, we recently showed that deletion of Gpb5 in mice does not result in abnormal regulation of the HPT axis during hypothyroidism and thyrotoxicosis (24).…”
mentioning
confidence: 99%
“…Thyrostimulin does not play a major role in the classical feedback regulation of the hypothalamo-pituitarythyroid (HPT) axis, as GPB5 knockout (GPB5 Ϫ/Ϫ ) mice do not have an abnormal thyroid phenotype and transcription of GPB5 is not regulated by thyroid hormone or thyrotropin-releasing hormone (TRH) (14,20). Furthermore, we recently showed that deletion of Gpb5 in mice does not result in abnormal regulation of the HPT axis during hypothyroidism and thyrotoxicosis (24).…”
mentioning
confidence: 99%